Political spots - Laybourne/Lemle Inc.; WQED (Television station : Pittsburgh, Pa.); Time-Life Video (New York : Time-Life Video, 1981)
"Blending wit and information, this program is a primer on the techniques used by today's political media makers."
Producer/Director, Alan Goldberg and Mickey Lemle.
Keywords: Television advertising -- Political aspects; Television and politics -- United States